Political and economic implications of the Turkish earthquakes: Centralisation of power has eroded state capacity - Hürcan Asl Aksoy; Salim Çevik (Stiftung Wissenschaft und Politik (SWP), 2023)
On 6 February 2023, Turkey was hit by one of the worst earthquakes in its history. Buildings were destroyed and damaged across the southern and eastern provinces. The official death toll is already over 50,000, and it is conceivable that the real numbers will be much higher. The earthquake also exposed the scale of political and institutional deterioration in Turkey. During Recep Tayyip Erdoægan's two decades in power, Turkey has experienced an enormous construction boom, evolved into an important player in humanitarian aid, and become an increasingly important regional military actor. However, the earthquake revealed that the highly centralised and personalised system of power had weakened state institutions and undermined their capacity to deliver. Turkey needs to reform its disaster management and governance. The European Union should assist the recovery and reconstruction efforts by targeting aid and using the momentum to mitigate anti-Westernism.
Keywords: 320; Turkey; earthquakes; death toll; Justice and Development Party (AKP); Recep Tayyip Erdoægan; construction boomregional military actor; state capacity; anti-Westernism; European Union